Esterase patterns and phylogenetic relationships of Drosophila species in the saltans subgroup (saltans group) - Nascimento, A. P.; Bicudo, HEMD (Kluwer Academic Publ, 2002)
The esterase patterns of sixteen strains from four species in the saltans subgroup were analyzed using polyacrylamide gel electrophoresis. Thirty-four esterase bands were detected. By using alpha and beta naphthyl acetates as substrates, they were classified in 18 alpha-esterases (they hydrolyse the alpha-naphtyl substrate), 15 beta-esterases (they hydrolyse the beta-naphtyl substrate) and 1 alpha/beta-esterase (it hydrolyses the alpha and beta-naphtyl substrates). Among the alpha-esterases, three were detected exclusively in males. Malathion, Eserine and pCMB were used as inhibitors in order to characterize biochemically the esterases. The results indicated the presence of cholinesterases, carboxylesterases and acetylesterases. The degree of mobility of the bands in the gels, their specificity to alpha and beta naphthyl acetates and the results of the inhibition tests allowed us to recognize tentatively nine genetic loci. Phylogenetic relationships among species inferred on the basis of the esterase patterns by PAUP 4.0 b8, with neighbor-joining search and a bootstrap analysis showed that, although the four species are closely related, D. septentriosaltans, D. saltans and D. austrosaltans are closer to each other than to D. prosaltans. These results showed to be consistent with phylogenetic relationships previously inferred from inversion polymorphism.
Keywords: Drosophila saltans subgroup; esterase patterns; phylogenetic relationships